Prevalence, Symptom Severity And Risk Factors Of Musculoskeletal Disorders Among Dental Therapists In Malaysia - Abdul Karim, Faizah; Abdul Razak, Ishak (IIUM Medical Journal Malaysia, 2017)
Introduction: Dental therapists are one of the main dental workforce in Malaysia and are exposed to various risk factors of MSD. However, studies on MSD among dental therapists are limited. The objectives of this study were to determine the prevalence, the sites affected, the symptom severity, the impact, the risk factors and the association between individual, biomechanical, physical and psychosocial risk factors with prevalence of MSD among dental therapists. Materials and Methods: A survey was conducted using self-administered questionnaire which was distributed to all dental therapists in Perak, Terengganu and Kuala Lumpur in February 2017, from which a response rate of 89.2% was achieved. Results: There was a high prevalence of MSD (87.5%) among the respondents. The MSD was found to be affecting mainly the back (69.7%), neck (66.7%), shoulders (58.7%) and wrists/hands (50.2%) while MSD of the elbow and lower extremities was found to more severe and often affect their daily work. Most of the respondents who reported MSD accommodated their own symptoms with analgesics or sought alternative treatment (20.1%). Majority reported that they often used vibratory instruments (76.1%), involved in biomechanical risk activities, and perceived that they have a high job demand and lack of authority to make decisions related to work. Age (OR: 3.58; 95% CI: 1.644, 7.773), number of extractions (OR: 4.69; 95% CI: 1.348, 16.327) as well as psychosocial factors (OR: 4.05; 95% CI: 1.547, 10.613) were significantly associated with prevalence of MSD. Conclusion(s): Therefore, preventive measures should be implemented to reduce the burden of MSD.